Asymptotic behavior of averaging of entire functions of improved regular growth - R.V. Khats’ (Karpatsʹkì Matematičnì Publìkacìï, 2013)
Using the Fourier series method for entire functions, we investigate the asymptotic behavior of averaging of entire functions of improved regular growth.